Legume integration and manure offer promise to improve early indicators of soil health - Visscher, Anna M; Fonte, Steven J; Ndangu, Samual Mathu; Mutai, Joyce; Six, Johan; Hartmann, Martin; Laub, Mortiz; Vanek, Steven; Travedi, Pankaj; Vanlauwe, Bernard; Pulleman, Mirjam (2024)
Tested indicators offer potential to detect that: • Cropping systems and manure play a crucial role in improving soil properties and potential microbial activity • Mineral nitrogen applications have a comparatively smaller impact on soil properties and potential microbial activity compared to main treatments • Legume integration provides a potential for both soil chemical properties and microbial activity • Carbon and nitrogen activity are key factors in driving critical microbial process